EVALUATION STUDY ABOUT SYNTHETIC NATURAL GAS - Abd Wahab, Mohd Elmie Farhan (Universiti Teknologi Petronas, 2010)
Today, natural gas is an important part of energy supply with electricity and for covering heat demand. Natural gas consumption, however, rises steadily all over the world, so that it is conceivable that there will be Oust like with crude oil) a noticeable shortage and dramatic price increases in the medium term. Increasing demand for natural gas and high natural gas prices in the recent past has led many to pursue unconventional methods of natural gas production. Natural gas that can be produced from coal or biomass is known as "synthetic natural gas" or "substitute natural gas" (SNG). SNG is a manufactured form of natural gas. Substitution of natural gas from renewable resources is therefore a necessity not only due to ecological reasons but also for economic reasons.